(untitled) (Research, Society and Development, 2023)
Botulinum toxin, derived from the Clostridium botulinum bacterium, has a multifaceted history, initially recognized for causing foodborne intoxications and more recently standing out for its therapeutic applications. Its mechanism of action, inhibiting the release of acetylcholine at neuromuscular junctions, results in temporary muscle paralysis, widely used in aesthetics to smooth wrinkles and enhance facial contours. Additionally, botulinum toxin has shown efficacy as an adjuvant in the treatment of facial neuropathic pain, providing relief to patients with conditions such as trigeminal neuralgia. The literature narrative review aims to deepen the understanding of this therapeutic application, analyzing clinical studies and systematic reviews to assess its effectiveness, safety, and mechanisms of action. The objective is to explore and consolidate the available evidence, identifying gaps in current knowledge and providing insights to guide future research and clinical practices in this specific field.